Recoveries of British-ringed Grey Lag Geese - Boyd, Hugh (Wildfowl, 1956)
Fifty Greylags were ringed in Iceland between 1932 and 1938 (Fuglamerkingar I-XV Ar, published by Nttrugripasafinio, Reykjavik, 1932-51). Thirteen were recovered. All had been ringed as juveniles. They had been captured in five localities in the north and three in the south of Iceland and were also widely scattered when found in Britain: eight in Scotland (Orkney one, Iverness one, Perthshire three, Dumfries two, Wigtown one) and five in Ireland (Wexford four, Kilkenny one). It could be inferred that the Iceland-breeding population winters in Britain and probably nowhere else and that though the breeding population consists, of necessity, of rather small widely-scattered colonies, the inhabitants of the various colonies probably do not remain segregated in winter.